El pez arco iris y la cueva de los monstruos - Pfister, Marcus; Gambolini, Gerardo (New York : Ediciones Norte-Sur, 2001)
In order to find healing algae for the ailing bumpy-backed fish, Rainbow Fish volunteers to brave the dreaded Sea Monsters' Cave.
K-3
Text in Spanish.
"First published in Switzerland under the title Der Regenbogenfisch hat keine Angst mehr"--P. facing t.p.
Keywords: Fishes -- Fiction; Spanish language materials; Fishes -- Fiction; Spanish language; Peces -- Ficción.